Tunnelling Effect for Quadruples Potential Using Matrix Propagation Method - Nasiroh, Chilwatun; Supriadi, Bambang; Handayani, Rif'ati Dina (Universitas Ahmad Dahlan, 2020)
Semiconductor materials can be used as potential barriers to Tunnelling effects. In this study, four semiconductor materials are arranged in various ways to form a quadruple potential structure to analyze the value of the transmission coefficient. The analysis was conducted using the analytical and numerical matrix propagation method using Matlab2018a. The results confirmed that the inverted arrangement produces the same transmission coefficient value for each energy. So that there are 12 kinds of transmission coefficient values generated from 24 arrangements. The semiconductor material composition with the most considerable transmission coefficient value is ADCB and BCDA, which have a value of 0.8087. The variation of the arrangement affects the value of the transmission coefficient so that it can be used as a guideline for selecting the arrangement that produces the most optimum value of the transmission coefficient from various possible arrangements.